Pengaruh Belanja Online dan Fitur Paylater Shopee Terhadap Perilaku Konsumtif Masyarakat Di Kota Surabaya - Tiara Ratnaningrum; Rina Dewi; Bambang Karnain; Harsono Teguh Santoso; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study examines the influence of online shopping and Shopee's paylater feature on the consumptive behavior of Surabaya residents. Conducted using a causal associative method and quantitative approach, the research involved 100 respondents selected through purposive sampling. Data was collected via online questionnaires and analyzed using multiple linear regression, descriptive analysis, normality testing, hypothesis testing, and determination coefficient testing. The results indicate that both online shopping and Shopee's paylater feature significantly impact consumptive behavior in Surabaya, with the paylater feature exerting a stronger influence. Recommendations include increasing promotion and education about Shopee's paylater feature, alongside governmental regulation for consumer protection and financial education.